Perancangan Aplikasi Panduan Pariwisata Kota Tasikmalaya pada Perangkat Bergerak Berbasis Android - Danial Ahmad Muslih; Rinta Kridalukmana; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2017)
Tourism is a valuable aspect of a region. The presence of the tourist areas will promote the welfare of the surrounding community. Information about the location of the tourist attractions in Tasikmalaya is still lacking and this is an obstacle for the tourists who will go sightseeing. Tasikmalaya tourism guide Application is built using Eclipse IDE with Java language. This application is created using PHP and MySql database. The design phase made is using Multimedia Development Life Cycle with UML modeling. The results obtained from this research is a tourism guide application that runs on Android operating system. The result shows that this application runs well on Ice Cream Sandwich version and more. Buttons and functions within the application have been running well with the respective functionality.